Dermatoscopic features of thin (≤2 mm Breslow thickness) vs. thick (>2 mm Breslow thickness) nodular melanoma and predictors of nodular melanoma versus nodular non‐melanoma tumours: a multicentric collaborative study by the International Dermoscopy Society. (24th August 2020) - Sgouros, D.; Lallas, A.; Kittler, H.; Zarras, A.; Kyrgidis, A.; Papageorgiou, C.; Puig, S.; Scope, A.; Argenziano, G.; Zalaudek, I.; Pizzichetta, M.A.; Marghoob, A.; et al.
Abstract: Background: Thin nodular melanoma (NM) often lacks conspicuous melanoma‐specific dermatoscopic criteria and escapes clinical detection until it progresses to a thicker and more advanced tumour. Objective: To investigate the dermatoscopic morphology of thin (≤2 mm Breslow thickness) vs. thick (>2 mm) NM and to identify dermatoscopic predictors of its differential diagnosis from other nodular tumours. Methods: Retrospective, morphological case–control study, conducted on behalf of the International Dermoscopy Society. Dermatoscopic images of NM and other nodular tumours from 19 skin cancer centres worldwide were collected and analysed. Results: Overall, 254 tumours were collected (69 NM of Breslow thickness ≤2 mm, 96 NM >2 mm and 89 non‐melanoma nodular lesions). Light brown coloration (50.7%) and irregular brown dots/globules (42.0%) were most frequently observed in ≤2 mm NMs. Multivariate analysis revealed that dotted vessels (3.4‐fold), white shiny streaks (2.9‐fold) and irregular blue structureless area (2.4‐fold) were predictors for thinner NM compared to non‐melanoma nodular tumours. Overall, irregular blue structureless area (3.4‐fold), dotted vessels (4.6‐fold) and serpentine vessels (1.9‐fold) were predictors of all NM compared to non‐melanoma nodular lesions. Limitations: Absence of a centralized, consensus pathology review and cases selected form tertiary centres maybe not reflecting the broader community. Conclusions: Our study sheds light into the dermatoscopic morphology of thin NM in comparison to thicker NM and could provide useful clues for its differential diagnosis from other non‐melanoma nodular tumours.